Quem quer que eu seja uma menina? Transgênero na infância - Nelson, Richardson Henrique (2024)
This master's dissertation investigates, based on the psychoanalytic theories of D. W. Winnicott and Robert J. Stoller, two public cases of boys who, during their second and third childhoods, dress as girls. The research starts from the hypothesis that transgender behavior in these cases has pre-Oedipal origins. These behaviors would be influenced by the unconscious maternal desire to have a girl, the absence of a paternal figure, the construction of a pathological false self due to the environmental intrusion, and the suspension or absence of the Oedipus complex. This study is a theoretical-clinical research. It is based on the case of B. presented in the book by Cassandra Pereira França, “Neither frog, nor princess: terror and fascination with the feminine, (Nem sapo, nem princesa: terror e fascínio pelo feminino, in the original).” and on the case of Sasha, reported in the documentary by French director and screenwriter Sébastien Lifshitz, titled “Little Girl” (Petite Fille, in the original). The study combines bibliographic research with the two mentioned cases and proposes a Winnicottian and Stollerian reinterpretation that does not necessarily coincide with the original analyses. From a Winnicottian perspective, it investigates the possibility that B. and Sasha developed a pathological false self in response to environmental intrusion and the unconscious desire of their mothers for them to be girls. From a Stollerian perspective, it considers the failure to achieve masculinity due to the blocks imposed by the mother during the disidentification process, which would result in a supposed suspension of the Oedipus complex